An Analysis of Predisposition Factors of Coated Tongue in Diponegoro National Hospital - Rachmawati, Dini (Journal of Oral Health Care, 2022)
Background: Several results of the study in Indonesia show that the age group of >45 years old has complaints of the coated tongue as the lesion with the highest percentage in the oral cavity. This occurs because the change of condition is influenced by the change of foods consumed, a decrease of saliva flow rate, and can be occurred due to the side effect of consuming antihypertensive drugs, smoking habits, and tongue brushing behavior. Objective: This study aims to find out the relationship between predisposition factors and coated tongue and find out the most contributing factors to coated tongue in the age group of >45 years old in Diponegoro National Hospital (RSND). Methods: This study used a cross-sectional design with 84 respondents of >45 years old in internal medicine polyclinic. This study was conducted by interviews of predisposition factors and TCI Shimizu for the assessment of coated tongue. The statistical test used the chi-square test and logistic regression test. Results: Respondents with a TCI value of >50% were 97.6%, and a TCI value of ?50% were 2.4%. Chi-square test showed that there is a relationship between coated tongue and xerostomia (P=0.034), brushing the tongue (P=0.001). However, there is no relationship between coated tongue and smoking (P=1.000), consuming antihypertensive drugs (P=1.000), consuming soft food (P=0.495). The results of the logistic regression test showed that xerostomia and brushing the tongue do not affect the coated tongue partially (P=0.997). Conclusion: There is a relationship between xerostomia and brushing the tongue with coated tongue. There is no partial effect between xerostomia and brushing the tongue with coated tongue.